Role of customary forest recognition and social trust in community-based biodiversity conservation in Bungo, Jambi, Indonesia - RIDWAN RIDWAN; SITI MARYAM; DEDI EPRIADI; RIZKI RIZKI; MD MAHMUDUL ALAM; SUSI PUSPITA SARI; ARWANSYAH KIRIN (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Ridwan, Maryam S, Epriadi D, Rizki, Alam MDM, Sari SP, Kirin A. 2025. Role of customary forest recognition and social trust in community-based biodiversity conservation in Bungo, Jambi, Indonesia. Biodiversitas 26: 4511-4521. Forests, including those governed by customary practices, are critical ecosystems that help maintain global climate balance. This study explores how customary forest recognition and social beliefs shape community behavior in protecting biodiversity in the Datuk Sinaro Putih customary forest in Jambi, Indonesia. Data were collected using a descriptive qualitative design through 17 semi-structured interviews with customary leaders, village officials, members of the Customary Forest Management Institution (LPHA), youth, community leaders, and non-governmental organizations from February to October 2024. Data were refined through participant observation and document analysis. The findings indicate that customary forest recognition and social beliefs are positively correlated with conservation behavior. Seloko Adat, the indigenous oral tradition of Datuk Sinaro Putih local community, serves as a symbolic and behavioral system, preserving traditional ecological knowledge, upholding customary law, and fostering intergenerational responsibility. This study highlights how the recognition of customary forests and social trust not only discourages extractive behavior through customary sanctions but also embeds conservation values ??into people's daily lives. These findings suggest that forestry policies should recognize and strengthen the functions of customary institutions through legal support, institutional strength, and sustainable financing schemes. Policies that incorporate customary principles, such as ecological prohibitions and collective farming practices, can enhance the legitimacy and success of conservation while safeguarding ecosystems. Future research should include a more comprehensive multi-level governance model that integrates local wisdom with national policies and the global biodiversity agenda, and analysis of economic, spiritual, and cosmological dimensions, as well as the relationships between customary institutions and external actors.